E-Cigarette Advice to Patients From Physicians and Dentists in the United States. Issue 5 (June 2018) - Drouin, Olivier; McMillen, Robert C.; Klein, Jonathan D.; Winickoff, Jonathan P.
Purpose: To report on adults' recall of discussion by physicians and dentists about e-cigarettes. Design: A nationally representative cross-sectional survey (Internet and random digit dialing) in the United States. Participants: Adults who ever used e-cigarettes. Measures: Participant-reported discussion about the potential benefits and harms of e-cigarettes with their doctor, dentist, or child's doctor in the past 12 months. Analysis: Fisher exact test for the analysis between benefits and harms for each type of provider and for rates of advice between provider types. Results: Among the 3030 adults who completed the survey, 523 (17.2%) had ever used e-cigarettes. Of those who had seen their doctor, dentist, or child's doctor in the last year, 7.3%, 1.7%, and 10.1%, respectively, reported discussing potential harms of e-cigarettes. Conversely, 5.8%, 1.7%, and 9.3% of patients who had seen their doctor, dentist, or child's doctor in the last year reported that the clinician discussed the potential benefits of e-cigarettes. Each clinician type was as likely to discuss harms as benefits. Rates of advice were similar between doctors and child's doctors but lower for dentists. Rates were comparable when the analysis was limited to current e-cigarette users, participants with children, or those who reported using both e-cigarettes and combusted tobacco. Conclusions: Few physicians and dentists discuss either the harms or benefits of e-cigarettes with their patients. These data suggest an opportunity to educate, train, and provide resources for physicians and dentists about e-cigarettes and their use.